Single-Shot Thoracic Spinal Anesthesia (TSA) pada Pasien dengan Abses Hepar Segmen VI Posterior untuk Operasi Laparascopy: Laporan Kasus - Yusmita, Dini; Ghozali, Imam; Rahmadilla, Alda Putri (CV. Jasa Sukses Abadi, 2024)
General anesthesia is the standard technique for operation. Due to many complication of general anesthesia, thoracic spinal anesthesia (TSA) is widely used for several operation. Thoracic segmental spinal anesthesia has been proven safe and effective for a variety of laparoscopic surgeries. Thoracal spinal anesthesia is also proven usefully in maintaining hemodynamics and reducing side effects. Laparoscopic surgery is an alternative to the drainage of liver abscess in addition to laparotomy. A 58-year-old man with a diagnosis of posterior segment VI of liver abscess lead a laparoscopic surgery which became a laparotomy under thoracic spinal anaesthesia. Thoracic spinal anesthesia with a median approach at the level of 9-10 intervertebral space (T9-10) single shot using a combination regimen of Isobaric 5 mg and Hyperbaric 2.5 mg, Fentanyl 50 mcg, Dexmetomidine 10 mcg, and Ketamine 20 mg. During the operation there were no hemodynamic fluctuations. Postoperative monitoring found the patient's condition was stable, pain control was good, and there were no postoperative complications such as headache, nausea, and vomiting. Single dose thoracal spinal anesthesia (TSA) is one of the regional anesthetic techniques of choice for abdominal surgery, especially in high-risk patients. In this patient it was found that TSA was effective and safe even though the surgical technique used was different. Monitoring during and postoperatively showed good results without any complications and significant hemodynamic fluctuations.